Nomophobia syndrome and its impact on morale and behavior change in early childhood - Kamil, Nurhusna; Narjis, Kalilah; Wahyuni, Sri (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
Nomophobia has become a prevalent issue which affects individuals today. This leads many to feel constantly connected to their devices. The term, derived from "No Mobile Phone Phobia," describes an excessive reliance on gadgets. This psychological condition is recognized as a global psychosocial phenomenon that influences mobile phone users and affects their morals and behavior. Alarmingly, this issue has also emerged among young children, with many preschoolers showing signs of addiction. This study is aimed at exploring the effects of nomophobia on early childhood, focusing on its moral and behavioral consequences in daily life. The study employed a qualitative case study approach and it involved two 5-year-old children. Data were collected through observations and unstructured interviews with their parents. The findings indicated that excessive gadget used in early childhood could significantly alter children's morals and behaviors. This was primarily due to insufficient parental supervision of their app usage. The study emphasized the need for intervention from adults, including both parents and teachers, who are the closest guardians to children in monitoring smartphone usage. These collaborative preventive measures to monitor and mitigate the negative impacts of smartphone usage are important to do. Future studies for exploring nomophobia in early childhood contexts are encouraged to delve deeper into the surrounding events and circumstances that affect children.